Pulsed magnetic field increases the effect of ultraviolet C radiation and thermal shock in aged yeasts - Mercado-Sáenz, Silvia; González-Vidal, Alejandro; Burgos-Molina, Antonio Manuel; López-Díaz, Beatriz; Sendra-Portero, Francisco; Ruiz-Gómez, Miguel José (Springer Nature, 2023)
The study of the effects of the magnetic field (MF) on living matter continues to be a dilemma. Until now, the interaction mechanisms of MF with living matter that explain the observed phenomena are unknown. Despite the existing literature and the multiple effects described to date, there are few published articles that study the combined effect of MF with other physical agents during the cellular aging process. In this sense, the aim of this work is to study whether low frequency and intensity pulsed and sinusoidal MF exposure produce alterations in the cell killing effect of ultraviolet C (UVC) radiation and thermal shock during the chronological aging of S. cerevisiae. Yeast cells were exposed to 2.45 mT (50 Hz) sinusoidal MF and 1.5 mT (25 Hz) pulsed MF, during 40 days of aging, in combination with UVC radiation (50 J/m2) and/or thermal shock (52°C). Cell survival was evaluated by clonogenic assay. The exposure of yeast to pulsed MF produces an acceleration of aging, which is not observed in cells exposed to sinusoidal MF. The pulsed MF modifies the cellular response to damaging agents only in aged S. cerevisiae cells. In this sense, the pulsed MF applied increases the damage induced by UVC radiation and by thermal shock. In contrast, the sinusoidal MF used has no effect.
“Plan Andaluz de Investi-gación, Desarrollo e Innovación (PAIDI); Junta de Andalucía”, code CTS-181.
Keywords: Campos magnéticos; Saccharomyces cerevisiae; Magnetic field; Heat shock; Ultraviolet C; Radiation; Yeast